A Cross-Sectional Study on Vocabulary Size Among Different Levels of the University Students - Tsuraya, Annisa Shofa; Atmowardoyo, Haryanto (Universitas Negeri Makassar, 2018)
The objectives of this research were to know students’ vocabulary size; and to know whether there was significant difference of vocabulary size among the students of different levels of English Education Department Faculty of Teacher Training and Education of Makassar Muhammadiyah University in academic year 2017/2018. This study used quantitative descriptive and cross-sectional study as the design of the study. The sample of this study were the first, third, fifth, and seventh semester students. The instrument of this study is a vocabulary size test. It used one-way ANOVA to analyze the data of the test. The findings reveal that the highest mean score was the seventh semester students and the lowest mean score was the third semester students. And the most beyond expectation was the mean score of the first semester students which gone over the third and fifth semester students’ mean score. There is significant difference of the vocabulary size among the students of different levels. The result showed F-value (F0) 11.11 is greater than F-table (Ft) 2.60, (11.11 ≥ 2.60). Then the p value is 0.000 lower than 0.05 (0.000 ≤ 0.05). Hence, it can be concluded that H0is rejected and H1is accepted. Post Hoc Multiple Comparison showed that significant difference did not exist between some groups and only exist between two groups. Clearly, from the result, it can be said that there was significant difference of vocabulary size among the university students of different levels of English Department of Makassar Muhammadiyah University.Keywords: vocabulary, vocabulary size test